Identification of circRNA–miRNA–Immune-Related mRNA Regulatory Network in Gastric Cancer - Wu, Zhenhai; Liu, Pengyuan; Zhang, Ganlu (Frontiers in Oncology, 2022)
The pathogenesis of gastric cancer (GC) is still not fully understood. We aimed to find potential regulatory network for ceRNA (circRNA-miRNA-immune-related mRNA) to uncover pathological molecular mechanisms of GC. The expression profiles of circRNA, miRNA and mRNA in the gastric tissue from GC patients were downloaded from the Gene Expression Omnibus (GEO) datasets. Differentially expressed circRNAs, miRNAs and immune-related mRNAs were filtered, followed by the construction of ceRNA (circRNA–miRNA–immune-related mRNA) network. Functional annotation and protein-protein interaction (PPI) analysis of immune-related mRNAs in the network was performed. Expression validation of circRNAs and immune-related mRNAs was performed in the new GEO and TCGA datasets and in vitro experiment. A total of 144 differentially expressed circRNAs, 216 differentially expressed miRNAs and 2392 differentially expressed mRNAs were identified in GC. Some regulatory pairs of circRNA–miRNA–immune-related mRNA were obtained, including hsa_circ_0050102-hsa-miR-4537-NRAS-Tgd cells, hsa_circ_0001013-hsa-miR-485-3p-MAP2K1-Tgd cells, hsa_circ_0003763-hsa-miR-145-5p-FGF10-StromaScore, hsa_circ_0001789-hsa-miR-1269b-MET-adipocytes, hsa_circ_0040573-hsa-miR-3686-RAC1-Tgd cells and hsa_circ_0006089-hsa-miR-5584-3p-LYN-neurons. Interestingly, FGF10, MET, NRAS, RAC1, MAP2K1 and LYN had a potential diagnostic value for GC patients. In the KEGG analysis, some signaling pathways were identified, such as Rap1 and Ras signaling pathways (involved NRAS and FGF10), Fc gamma R-mediated phagocytosis and cAMP signaling pathway (involved RAC1), proteoglycans in cancer (involved MET), T cell receptor signaling pathway (involved MAP2K1) and chemokine signaling pathway (involved LYN). The expression validation of hsa_circ_0003763, hsa_circ_0004928, hsa_circ_0040573, FGF10, MET, NRAS, RAC1, MAP2K1 and LYN was consistent with the integrated analysis. In conclusion, identified ceRNA (circRNA-miRNA-immune-related mRNA) regulatory network may be associated with the development of GC.